Benefits Of Using E-Learning In Micro Teaching Courses - Sri Handayani Parinduri (Gravity Journal, 2025)
The purpose of this research is to analyze the benefits of using e-learning in micro teaching courses. This type of research is descriptive qualitative using survey research procedures through literature study and field study. Literature study was conducted through literature search from books and reputable online sites. Field studies were conducted through observations related to the benefits provided by the use of e-learning for 6th semester students in micro teaching courses. The results showed that there were positive benefits obtained by students from the use of e-learning in micro teaching courses